Impacto de la puesta en marcha del megaproyecto puerto de chancay en Perú en la logística del comercio internacional en sur América (2024)
Seaports play an essential role in international trade, which makes it important to have basic characteristics such as draft, infrastructure, Teu capacity, location, to be effective in logistics and carry out compliance in the supply chain Supply. The launch of the Chancay megaport in Perú allows us to visualize the perspective on the impact it has on South América since in addition to its strategic location, it has the port capacity and depth to receive the largest container ships in maritime transport, and as In this way it can be a complement to the ports of the region or become a port Hub.